A review on eye diseases induced by blue light: pathology, model, active ingredients and mechanisms - Yan, Yuan; Wu, Yiyao; Zhao, Yu; Yang, Yaguang; An, Guangtao; Liu, Zhidong; Qi, Dongli (Frontiers in Pharmacology, 2025)
Blue light induced eye damage (BLED) belongs to modern diseases. It is an ophthalmic disease caused by prolonged exposure to electronic devices or screens containing a large amount of high-energy short waves (blue light). Specific symptoms include dryness and discomfort in the eyes, blurred vision, headache, insomnia, and in severe cases, it may also cause various eye diseases such as cataracts and glaucoma. At present, the development of health products and drugs for eye blue light injury faces many difficulties. Therefore, further exploration and research are needed on the pathogenesis, pathophysiology, and pharmacological mechanisms of blue light injury. Natural medicine ingredients and preparations have unique advantages in targeting eye blue light injury fatigue products due to their multi-component synergistic effects, overall regulation, and mild and safe characteristics. Starting from the disease-related mechanisms and pathophysiological characteristics of eye blue light injury, this article elucidates the pharmacological mechanisms of various drugs for treating eye blue light injury. At the same time, it reviews the research on in vitro cultured cell and animal model conditions for blue light injury eyes, in order to provide reference for subsequent blue light injury modeling experiments. And explore future research directions to provide new ideas and methods for the prevention and treatment of BLED.